2022
DOI: 10.3390/biom12111696
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Kinetic Analysis and Pharmacophore-Directed Discovery of 3-Ethylaniline Hybrid Imino-Thiazolidinone as Potential Inhibitor of Carbonic Anhydrase II: An Emerging Biological Target for Treatment of Cancer

Abstract: Carbonic anhydrases (CA), having Zn2+ metal atoms, are responsible for the catalysis of CO2 and water to bicarbonate and protons. Any abnormality in the functioning of these enzymes may lead to morbidities such as glaucoma and different types of cancers including brain, renal and pancreatic carcinomas. To cope with the lack of presence of a promising therapeutic agent against these cancers, searching for an efficient and suitable carbonic anhydrase inhibitor is crucial. In the current study, ten novel 3-ethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Additionally, abundant in numerous tissues, CA II is important in many disease states, including glaucoma, epilepsy, edema, high altitude condition, and kidney illness [7] . Furthermore, several tumor cells and cell lines have been found to exhibit CAI and CAII [8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, abundant in numerous tissues, CA II is important in many disease states, including glaucoma, epilepsy, edema, high altitude condition, and kidney illness [7] . Furthermore, several tumor cells and cell lines have been found to exhibit CAI and CAII [8] …”
Section: Introductionmentioning
confidence: 99%
“…[7] Furthermore, several tumor cells and cell lines have been found to exhibit CAI and CAII. [8] The heterocycles that include nitrogen are among a group of substances with a wealth of practical uses. Small-molecule pharmaceuticals of fused nitrogen heterocycles make up 59 % of U.S. FDA-approved medicines, particularly in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Compound (26e) exhibited better inhibitory activity against CA II with IC 50 value 1.545 ± 0.016 mM (Scheme 7). 50 Amantadine thiazolidinone derivatives synthesized by Ahmad et al were found to exhibit good inhibitory activity against the enzyme elastase with IC 50 values ranging from 0.221 ± 0.059 to 3.257 ± 0.541 mM. Compound 5 g showed highest potency against elastase with an IC 50 value of 0.124 ± 0.022 mM which was 50 times higher than Oleanolic acid's value of 5.996 ± 0.882 mM.…”
Section: Biological Aspectsmentioning
confidence: 99%
“…49 Ahmed et al synthesized a series of iminothiazolidinone derivatives (26a-j) by reacting equimolar amount of acyl thioureas (24a-j) and ethyl 4-ethoxypent-4-en-2-ynoate (25) in dry methanol as solvent at room temperature (Scheme 7). 50 The same procedure was applied with success for the preparation of a novel series of amantadine thiazolidinones analogs from acyl thioureas and ethyl 4-ethoxypent-4-en-2-ynoate. 51 A new methodology was developed by Pokotylo et al for the synthesis of 2H-1,3,5-oxadiazine-2,4(3H)-diimines derivatives (30a-g) by dehydrosulfurization of acyl thiourea (29a-g) with dicyclohexyl carbodiimide.…”
Section: Heterocyclization Reactionsmentioning
confidence: 99%
“…Disorders associated with this enzyme lead to the development of glaucoma, as well as a number of cancers. In their work [ 8 ], Ahmed et al describe the development of a number of inhibitors of the carbonic anhydrase as potential therapeutic agents. Based on results obtained from vitro and in in silico screening, the authors propose the most promising drug candidate.…”
mentioning
confidence: 99%